Status quo and future trends of BIM-based coordination research: a critical review - Wu, Zezhou; Deng, Kaiwen; Chen, Changhong; Li, Heng; Antwi-Afari, Maxwell Fordjour; Wang, Ying (Journal of Civil Engineering and Management, 2022)
Enhancing coordination between stakeholders is a critical function of Building Information Modeling (BIM). Recently, there have been numerous studies investigating BIM-based coordination; however, no explicit attempt has been made to investigate the current status of relevant research and determine the future directions. Hence, this study examines the BIM-based coordination literature published from 2006 to 2020 through bibliometric literature searching, scientific mapping, and in-depth critical analysis to fill the research gap. After a comprehensive filtering process, 656 pieces of literature were collected from Scopus. To map the representative information in the BIM-based coordination research, the determination and visualization of the most influential scholars, journals, countries/regions, and articles, as well as their importance and relationships, were performed through VOSviewer. Four emerging research topics were further discussed according to the determined scientific map. Moreover, a framework that presents the existing research gaps and future research directions was proposed. This research provides a clear picture of the leading information and future research trends of the BIM-based coordination, contributing to the body of knowledge theoretically and offering references for related stakeholders practically.